Impact of Motivation Determinants on Innovative Social Project Management Performance:The Role of Power Skills - Abou-hafs, Habiba; Afras, Houriya; Rachid, Tatouti (Archives of Business Research, 2024)
This research was carried out to study the impact of autonomy, feedback, and task interest and job emotion on the innovative social project management performance. Based on a quantitative study conducted with 80 managers of innovative social projects, the present study attempts to identify the impact of intrinsic motivation determinants witch are considered power skills on innovative social project management performance. Descriptive analysis, principal component analysis, regression analysis and structural equations were used to classify, categorize and measure the impact between variables. Results were analyzed using SPSS.25 and Smart PLS 3. The results concluded that the all-path coefficient showed positive values ​​of the three motivation determinants witch are components of power skills (autonomy, feedback and professional emotions) supported the impact directions as postulated in the hypotheses. Except Task interest did not have a significant direct impact on project performance (ß =0,091; P=0,164) and on job emotion (ß =0,151; P=0,092).